Screening Of Ach Ease Inhibition In Blood Plasma And Brain Of Wistar Rats By Neurella D (Combination Pesticide) - Dr.H.SEKAR BABU; Dr.P.JAYARAMAN; P.AARTHY (International Journal of Pharma and Bio Sciences, 2010)
Ach Ease is a very important biomarker to asses the lesions in the nervous caused by pesticides organophosphates and pyrethroids. The present trend in agriculture is to control pest animals invading the agricultural commodities. Farmers use combination pesticide containing one organophosphate and a pyrtheroids to have a best pesticidal action and at the same time to reduce environmental toxicity. in human and domestic animals. Many works have been attributed regarding screening the toxicity of the constituent pesticide [organophosphate or pyrethroids of the combination] but less exploration is done on the sub acute toxicity a combination pesticide. Hence the present work has been designed to study the sub acute toxicity for 28 days on wistar stain rats to screen the biomarker AchEase enzyme inhibition in the plasma and in brain .Results are quite interesting to note that the toxicity exhibited by the mixed formulation differ from the toxicity exhibited by its constituents. In lower doses the combination pesticide did not showed significant inhibition in AchEase activity due to synergetic effect whereas in the earlier literature inhibition is seen in all the experimental groups with relation to its constituent pesticide in the selected combination pesticide. Therefore it is very much necessary that all the toxicological studies have to be carried out (as for a new pesticide) for a combination pesticide before it can be brought to the field. Similar subacute studies on AChEase inhibition will help us to identify a combination pesticide that have better efficacy in pest control. With lesser mammalian toxicity compared to its constituents in the combination.